Soft skills in design education, identification, classification, and relations: Proposal of a conceptual map - Nazaré de Freitas, Ana Paula; Assoreira Almendra, Rita (Design and Technology Education: An International Journal, 2021)
Soft skills are interpersonal, social, and emotional competencies, transversal to various fields of knowledge and life. In the Knowledge Age, soft skills play an essential role in the differentiation of human work. Nevertheless, in design education, there are still few studies on soft skills. This study brings a conceptual map of soft skills in design education. It refers to a mixed-methods research conducted through a survey involving 93 teachers of high education design courses in 26 countries. We combined the survey results with a literature review analysis aimed at defining constructs and identifying their relationship. Finally, we propose a classification for soft skills as being Collective/Individual and Cognitive-Metacognitive/Interpersonal-Social. Our research recognises the connections and interdependence among skills, allowing us to settle different groups and establish relations among other skills. Furthermore, based on literature, we identified a hierarchy of gateways skills and high order skills and pointed out their connections. Additionally, a conceptual map was created, including the 20 primary soft skills in design education, their proposed classification, and the links between the skills. The result can help teachers and students know the primary soft skills in design education and develop teaching-learning approaches to acquire soft skills during their university training.